Pengaruh Pemberian Silase Komplit Berbasis Sorgum dan Clitoria Ternatea Hasil Integrasi Tanaman Holtikultura yang Berbeda terhadap Konsumsi serta Kecernaan Protein Kasar dan Serat Kasar Kambing Betina Lokal - Bediona, Petronela; Maranatha, Grace; Amalo, Daud (Yayasan Sumber Daya Manusia Cerdas, 2024)
The aim of this study was to determine the effect of blood metabolite concentrations on Ongole x Brahman cross cattle fed kume grass silage and Alycicarpus vaginalis at different balances. The livestock used were 4 Ongole x Brahman cattle with an average body weight of 167.25 kg (KV = 15.6%) with an age range of 8-12 months and a body weight of 171,5-200 kg. This research was carried out using the experimental method with the Latin square design (RBSL) with 4 treatments and 4 replications. The treatments in this study were AV0 = Silage 70% Kume Grass + 30% concentrate, AV20 = Silage 56% Kume Grass + 14% Alysicarpus vaginalis + 30% Concentrate, AV40 = Silage 42% Kume Grass + 28% Alysicarpus vaginalis + 30% Concentrate, AV60 = Silage 28% Kume Grass + 42% Alysicarpus vaginalis + 30% Concentrate. Data were analyzed using analysis of variance (ANOVA). The results showed blood glucose concentrations AV0=69.94±2.83 mg/dl, AV20=76.23±2.23 mg/dl, AV40= 74.57±6.41 mg/dl, AV60=71.96±2.51 mg/dl. Blood Urea concentration AV0= 42.08±1.74mg/dl, AV20= 42.08±180mg/dl, AV40= 40.93±1.24mg/dl, AV60= 43.46±0.75mg/dl. Total Plasma Protein AV0= 6.55±0.30mg/dl, AV20= 6.35±0.34mg/dl, AV40= 6.35±0.34mg/dl, AV60= 6.80±0.00mg/dl. Based on the analysis of variance, it showed that the treatment had no significant effect (P>0.05) on blood glucose, blood urea and total plasma protein. It was concluded that the administration of kume grass silage and Alysicarpus vaginalis with different balances showed relatively the same results on blood glucose concentration, blood urea concentration and total plasma protein in Ongole x Brahman cross cattle so that they could be used as alternative feed.